The Composite Regulatory Basis of the Large X-Effect in Mouse Speciation. (26th December 2016) - Larson, Erica L.; Keeble, Sara; Vanderpool, Dan; Dean, Matthew D.; Good, Jeffrey M.
Abstract : The disruption of meiotic sex chromosome inactivation (MSCI) has been proposed to be a major developmental mechanism underlying the rapid evolution of hybrid male sterility. We tested this idea by analyzing cell-specific gene expression across spermatogenesis in two lineages of house mice and their sterile and fertile reciprocal hybrids. We found pervasive disruption of sex chromosome gene expression in sterile hybrids at every stage of spermatogenesis. Failure of MSCI was developmentally preceded by increased silencing of autosomal genes, supporting the hypothesis that divergence at the hybrid incompatibility gene, Prdm9, results in increased rates of autosomal asynapsis which in turn triggers widespread silencing of unsynapsed chromatin. We also detected opposite patterns of postmeiotic overexpression or hyper-repression of the sex chromosomes in reciprocal hybrids, supporting the hypothesis that genomic conflict has driven functional divergence that leads to deleterious X–Y dosage imbalances in hybrids. Our developmental timeline also exposed more subtle patterns of mitotic misregulation on the X chromosome, a previously undocumented stage of spermatogenic disruption in this cross. These results indicate that multiple hybrid incompatibilities have converged on a common regulatory phenotype, the disrupted expression of the sex chromosomes during spermatogenesis. Collectively, these data reveal a composite regulatory basis to hybrid male sterility in mice that helps resolve the mechanistic underpinnings of the well-documented large X-effect in mice speciation. We propose that the inherent sensitivity of spermatogenesis to X-linked regulatory disruption has the potential to be a major driver of reproductive isolation in species with chromosomal sex determination.